People's Republic of China-Hong Kong Special Administrative Region : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for People's Republic of China-Hong Kong Special Administrative Region. (IMF Staff Country Reports; Country Report ;, 2016)
This 2015 Article IV Consultation highlights that the growth of Hong Kong Special Administrative Region is expected at 2.25 percent in 2015, with domestic demand acting as the principal source of momentum. Growth is likely to pick up modestly to 2.5 percent in 2016, with a smaller drag from external demand reinforcing resilient domestic demand. Inflation has declined and is expected to remain below 3 percent in 2015-16 on softer commodity prices. The current account has dropped to about 2.5 percent of GDP, but is projected to improve to about 3.5 percent over the medium term as the global economy recovers.